(untitled) (Pesticides and Phytomedicine / Pesticidi i fitomedicina, 2016)
The impact of three conventional chemical preservatives (sodium benzoate, potassium sorbate and salicylic acid) and a natural antimicrobial compound (thymol) on germination, dynamics of growth and accumulation of fresh biomass (g per seedling) of Lactuca sativa L., cultivar Great Lakes, was studied under laboratory conditions. The tested conventional chemical preservatives demonstrated strong inhibitory effects (GI 27.1-0.0%) on germination and initial development of L. sativa, and they cannot be used in allelopathic studies in the laboratory. An addition of thymol at 0.5-1.0 ‰ concentration showed no inhibitory effect (GI varied 81.7-84.6%) on germination and initial development of L. sativa. Thymol can therefore be used as a natural antimicrobial compound in allelopathic studies in the laboratory.